Biomarkers for PD-1/PD-L1 Blockade Therapy in Non–Small-cell Lung Cancer: Is PD-L1 Expression a Good Marker for Patient Selection? - Chae, Young Kwang; Pan, Alan; Davis, Andrew A.; Raparia, Kirtee; Mohindra, Nisha A.; Matsangou, Maria; Giles, Francis J. (Clinical lung cancer, 2016)
Immunotherapy has emerged as a promising treatment modality in cancer therapy. With improved understanding of how to tip the balance of immune homeostasis, novel therapeutics targeting immune checkpoints have been developed, with durable responses observed in multiple solid tumors, including melanoma, renal cell carcinoma, and non–small-cell lung cancer. Clinical trials have reported favorable responses using programmed cell death-1 protein receptor (PD-1)/programmed cell death-1 protein ligand (PD-L1) blockade as monotherapy and most impressively in combinatorial trials with cytotoxic T-lymphocyte antigen-4 protein blockade. Nonetheless, a clinical benefit has not been observed in all patients. Therefore, identifying the ideal biomarkers for patient selection would be of great value in optimizing and personalizing immunotherapy. The utility of PD-L1 expression as a biomarker has varied in different clinical trials and immunohistochemistry assays. In addition, the response to immune checkpoint inhibition has been complicated by PD-L1 expression as a marker influenced by the dynamic tumor microenvironment. No consensus has yet been reached on whether PD-L1 expression is an ideal marker for patient selection. Recent research has shown promise for alternative markers, including T-cell immunohistochemistry, other immunologic markers, T-cell receptor clonality, and somatic mutational burden. However, additional studies are needed to assess the value of these as practical predictive biomarkers for patient selection and treatment response.